2007
DOI: 10.1111/j.1742-4658.2007.05726.x
|View full text |Cite
|
Sign up to set email alerts
|

Cupiennin 1a, an antimicrobial peptide from the venom of the neotropical wandering spider Cupiennius salei, also inhibits the formation of nitric oxide by neuronal nitric oxide synthase

Abstract: Cupiennin 1a (GFGALFKFLAKKVAKTVAKQAAKQGAKYVVNKQME-NH2) is a potent venom component of the spider Cupiennius salei. Cupiennin 1a shows multifaceted activity. In addition to known antimicrobial and cytolytic properties, cupiennin 1a inhibits the formation of nitric oxide by neuronal nitric oxide synthase at an IC50 concentration of 1.3 +/- 0.3 microM. This is the first report of neuronal nitric oxide synthase inhibition by a component of a spider venom. The mechanism by which cupiennin 1a inhibits neuronal nitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Remarkably, Cu1a exhibits a second, non-membranolytic activity: in the submicromolar range, the peptide inhibits the formation of nitric oxide by neuronal nitric oxide synthase through complexation with the regulatory protein Ca 2? calmodulin (Pukala et al 2007b). This indicates that the targets of Cu1a in a spider's prey are not only the cell membranes, but also cellular enzymes.…”
Section: Introductionmentioning
confidence: 98%
“…Remarkably, Cu1a exhibits a second, non-membranolytic activity: in the submicromolar range, the peptide inhibits the formation of nitric oxide by neuronal nitric oxide synthase through complexation with the regulatory protein Ca 2? calmodulin (Pukala et al 2007b). This indicates that the targets of Cu1a in a spider's prey are not only the cell membranes, but also cellular enzymes.…”
Section: Introductionmentioning
confidence: 98%
“…Antimicrobial peptides serve as a first line of defense against invading pathogens, and are involved in modulating the host signaling mechanisms of the immune response [2]. Previous studies have shown that several antimicrobial peptides inhibit the formation of nitric oxide by interacting with or affecting nitric oxide synthase; such peptides include caerin [3e5], cupiennin [6], dahlein [5], frenatin [5,7], and citropin [8]. An a-helical antimicrobial peptide, named moronecidin or piscidin (PCD)-1, was previously isolated from the skin and gills of hybrid striped bass [1].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, membranolytic activity was reported for cytolytic LP. In addition, cupiennin 1a was shown to inhibit nitric oxide formation by neuronal nitric oxide synthase through complexation with the regulatory protein calmodulin [50].…”
Section: Introductionmentioning
confidence: 99%